The Description of The Social Capital in Ecotourism Village Case Study in Tambaksari Village, Pasuruan District, East Java - Rukavina Baksh (AGROLAND The Agricultural Sciences Journal (e-Journal), 2015)
The objective of the study was to describe the social capital of the community in the Tambaksari Village. There were as many as 170 people involved in the study. The data were then analyzed using descriptive statistics. The results show that the local community of Desa Tambaksari agreed networking and norms had been implemented higly, while trust and paticipation were implemented at medium level in the development of ecotourism. Therefore, trust and participation need to be improved.